2013
DOI: 10.1186/1471-244x-13-96
|View full text |Cite
|
Sign up to set email alerts
|

Socio demographic profile and utilization pattern of antipsychotic drugs among schizophrenic inpatients: a cross sectional study from western region of Nepal

Abstract: BackgroundCurrently a large number of atypical antipsychotics available in the market are endorsed as better option for treating schizophrenia than the typical antipsychotics. Information regarding the utilization pattern of antipsychotic drugs is lacking in Nepalese population particularly in Western Nepal. By means of this study one is expected to acquire an idea concerning clinician’s preference to the antipsychotic drugs in actual clinical setup. The main objective of the study was to find the commonest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 28 publications
(34 reference statements)
8
34
2
Order By: Relevance
“…Our result was similar to the study conducted by Banerjee et.al where 58.76% of males and 41.24% of females suffered from schizophrenia. 8 Our results were also similar to a multicentric study, conducted by MY Chong et.al where male predominance was consistent accounting for 55.9% of cases. 9 Most of the schizophrenics were <40years (70%) and the average age was 35.6 years.…”
Section: Demographic Details and Schizophreniasupporting
confidence: 81%
See 1 more Smart Citation
“…Our result was similar to the study conducted by Banerjee et.al where 58.76% of males and 41.24% of females suffered from schizophrenia. 8 Our results were also similar to a multicentric study, conducted by MY Chong et.al where male predominance was consistent accounting for 55.9% of cases. 9 Most of the schizophrenics were <40years (70%) and the average age was 35.6 years.…”
Section: Demographic Details and Schizophreniasupporting
confidence: 81%
“…Similar results were seen with a study conducted by Banerjee et.al where 78.6% were <40years and 21.4% were >40years. 8 But different results were observed by the study conducted in Japan by S Cheung et.al, where the average age of patients suffering with schizophrenia was 61.9 years.…”
Section: Demographic Details and Schizophreniamentioning
confidence: 39%
“…8,9,20,21 About 70% of the patients were unemployed in this study. Some studies that determined the employment status of patients with schizophrenia who were on antipsychotics found that the majority of them were unemployed.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies that determined the employment status of patients with schizophrenia who were on antipsychotics found that the majority of them were unemployed. 8,9 Employment rates among patients with schizophrenia are low, with an estimate from a European study ranging from 8 to 35%. 22 Individual factors (such as job histories), illness-related factors (such as illness severity) and societal conditions (such as discrimination and social welfare policy) are all potential contributors to variations in employment rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation